Tinjauan Hukum Pelaksanaan Perjanjian Pengadaan Perumahan Oleh Developer Di PT. Bank Niaga - Israq, Nabilah; Anjeli Afriani; Lutfiah Azizah; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
In the property world, housing procurement agreements between developers and banking institutions such a PT Bank Niaga play an important role in supporting the provision of affordable and quality housing for the community. However, the implementation of this agreement pften raises various legal challenges, both for developers and banks, which can affect the smoothness of the procurement process. Therefore, this study examines housing procurement agreements with a normative legal approach that includes the regulations of Law Number 1 of 2011 concerning Housing and Residential Areas and the regualtions of the Financial Services Authority (OJK), which are expected to provide a deeper understanding of the legal basis, procedures, right, obligations and risks involved in the legal relationship between the two parties. The purpose of this paper is to explore the implementation of housing procurement agreements by developers at PT Bank Niaga, with a focus on the legal aspects and implications of practies in the field. The results of the study indicate that housing procurement agreements by developers at PT Bank Niaga have generally referred to the applicable legal framework, this study highlights the importance of implementing prudential principles by PT Bank Niaga in financing housing procurement projects. At the same time, it is emphasized that the implementation of the housing procurement agreements by developers at PT Bank Niaga requires stronger legal certainty and strengthening of supervision in its implementation.